ECONOMIC RELATIONS BETWEEN ROMANIA AND VIETNAM (1975 –1989) - Nguyen The Ha (Romanian Journal of Historical Studies, 2023)
The main purpose of this article is to clarify some aspects regarding the economic relations between Romania and Vietnam in period 1975–1989. In order to achieve this proposed aim, were analysed a series of documents originating from the National Archives of Romania and also from the Center for Diplomatic Archives of the Ministry of Foreign Affairs of Romania. Thus, to achieve this objective, qualitative and quantitative research methods were used, as well as other methods such as as historical, logical, synthesis, and document analysis. The research undertaken has been focused in the first stage on agreements establishing economic cooperation between two states, then the emphasis being on cooperation in some industries and cooperation in the area of trade exchange. In this connection, the results of the study can be a valuable reference for the history of diplomatic relations between Romania and Vietnam, as well an important working tool for the study of the international relations history